2021
DOI: 10.3390/vaccines9030272
|View full text |Cite
|
Sign up to set email alerts
|

Design of Alphavirus Virus-Like Particles Presenting Circumsporozoite Junctional Epitopes That Elicit Protection against Malaria

Abstract: The most advanced malaria vaccine, RTS,S, includes the central repeat and C-terminal domains of the Plasmodium falciparum circumsporozoite protein (PfCSP). We have recently isolated human antibodies that target the junctional region between the N-terminal and repeat domains that are not included in RTS,S. Due to the fact that these antibodies protect against malaria challenge in mice, their epitopes could be effective vaccine targets. Here, we developed immunogens displaying PfCSP junctional epitopes by geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…To address this, we produced a prototypical immunogen using an approach from the field of HIV-1 vaccine research (Xu et al, 2018) and found that a junctional epitope-focused immunization strategy induced a strong response from H iGL-CIS43 k iGL-CIS43 B cells. This is in agreement with two recent studies showing that the junctional epitope, when displayed on an alphavirus viruslike particle (VLP) (Francica et al, 2021) or Qb bacteriophage VLPs (Jelı ´nkova ´et al, 2021), elicits partial protection against (B) Crystal structures of junctional peptide (peptide 21) in complex with the most potent iGL-CIS43-derived antibodies from m42 and m43, highlighting similarity in SHM (left) and variation in bound epitope, especially in relationship to isoleucine or leucine at HC position 98 (right). Numbering on peptide 21 corresponds to the PfCSP numbering.…”
Section: Discussionsupporting
confidence: 93%
“…To address this, we produced a prototypical immunogen using an approach from the field of HIV-1 vaccine research (Xu et al, 2018) and found that a junctional epitope-focused immunization strategy induced a strong response from H iGL-CIS43 k iGL-CIS43 B cells. This is in agreement with two recent studies showing that the junctional epitope, when displayed on an alphavirus viruslike particle (VLP) (Francica et al, 2021) or Qb bacteriophage VLPs (Jelı ´nkova ´et al, 2021), elicits partial protection against (B) Crystal structures of junctional peptide (peptide 21) in complex with the most potent iGL-CIS43-derived antibodies from m42 and m43, highlighting similarity in SHM (left) and variation in bound epitope, especially in relationship to isoleucine or leucine at HC position 98 (right). Numbering on peptide 21 corresponds to the PfCSP numbering.…”
Section: Discussionsupporting
confidence: 93%
“…However, the isolation of rare and potent mAbs that preferentially bind NPDP (Kisalu et al, 2018;Tan et al, 2018) or the NVDP repeats (Wang et al, 2020) identified these subdominant epitopes as sites of vulnerability on PfCSP. As these epitopes are not contained in RTS,S, these discoveries led to the development of next-generation vaccines against the junctional region (Atcheson et al, 2021;Calvo-Calle et al, 2021;Francica et al, 2021;Jelı ´nkova ´et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the isolation of rare and potent mAbs that preferentially bind NPDP (Kisalu et al, 2018;Tan et al, 2018) or the NVDP repeats (Wang et al, 2020) identified these subdominant epitopes as new sites of vulnerability on PfCSP. As these epitopes are not contained in RTS,S, these discoveries led to the development of nextgeneration vaccines against the junctional region (Atcheson et al, 2021;Calvo-Calle et al, 2021;Francica et al, 2021;Jelínková et al, 2021).…”
Section: Introductionmentioning
confidence: 99%